Persistent High Percentage of HLA-DR+CD38high CD8+ T Cells Associated With Immune Disorder and Disease Severity of COVID-19 - Du, Juan; Wei, Lirong; Li, Guoli; Hua, Mingxi; Sun, Yao; Wang, Di; Han, Kai; Yan, Yonghong; Song, Chuan; Song, Rui; Zhang, Henghui; Han, Junyan; et al. (Frontiers in Immunology, 2021)
Background The global outbreak of coronavirus disease 2019 (COVID-19) has turned into a worldwide public health crisis and caused more than 100,000,000 severe cases. Progressive lymphopenia, especially in T cells, was a prominent clinical feature of severe COVID-19. Activated HLA-DR+CD38+ CD8+ T cells were enriched over a prolonged period from the lymphopenia patients who died from Ebola and influenza infection and in severe patients infected with SARS-CoV-2. However, the CD38+HLA-DR+ CD8+ T population was reported to play contradictory roles in SARS-CoV-2 infection. Methods A total of 42 COVID-19 patients, including 32 mild or moderate and 10 severe or critical cases, who received care at Beijing Ditan Hospital were recruited into this retrospective study. Blood samples were first collected within 3 days of the hospital admission and once every 3–7 days during hospitalization. The longitudinal flow cytometric data were examined during hospitalization. Moreover, we evaluated serum levels of 45 cytokines/chemokines/growth factors and 14 soluble checkpoints using Luminex multiplex assay longitudinally. Results We revealed that the HLA-DR+CD38+ CD8+ T population was heterogeneous, and could be divided into two subsets with distinct characteristics: HLA-DR+CD38dim and HLA-DR+CD38hi. We observed a persistent accumulation of HLA-DR+CD38hi CD8+ T cells in severe COVID-19 patients. These HLA-DR+CD38hi CD8+ T cells were in a state of overactivation and consequent dysregulation manifested by expression of multiple inhibitory and stimulatory checkpoints, higher apoptotic sensitivity, impaired killing potential, and more exhausted transcriptional regulation compared to HLA-DR+CD38dim CD8+ T cells. Moreover, the clinical and laboratory data supported that only HLA-DR+CD38hi CD8+ T cells were associated with systemic inflammation, tissue injury, and immune disorders of severe COVID-19 patients. Conclusions Our findings indicated that HLA-DR+CD38hi CD8+ T cells were correlated with disease severity of COVID-19 rather than HLA-DR+CD38dim population.